Unified Compact Formulas of Output Characteristics for External Hydraulic Gear-motors - Liu Ping; Li Yulong; Hou Xinyu; Zhang Lihua (Jixie chuandong)
In order to correctly understand the output characteristics of gear-motors with different types of backlash sizes/offset unloading slots, a unified simplified formula for output characteristics such as speed/torque is constructed based on the different meshing line intervals of meshing tooth profiles/output characteristics, using the type value that measures the backlash size and the offset value between the symmetrical line of the double unloading slots and the centerline of the gear pair as variables. The results show that through the interval of the output characteristic meshing-line, the output speed and torque curve can be directly obtained from the speed and torque curve of meshing tooth-profile; under the symmetrical relief-groove type, the average output speed is the smallest, the average torque is the biggest, and the ripple coefficients of the output speed and torque are the smallest; the offset range of the relief-groove and the range of the output speed and torque regulating are larger under small backlash type than large backlash type; with small backlash and symmetrical relief-groove type, the average output speed is smaller, the average output torque is larger, and the ripple coefficient of the output speed and torque is smaller; the torque-ripple coefficient of the gear-motor is completely consistent with the flow-ripple coefficient of the gear-pump; the torque-ripple coefficient is slightly less than the speed-ripple coefficient, and can be approximately equal under the condition of large tooth-number; when high-speed is pursued, the type combination of large backlash and relief groove limit-offset shall be selected; with the pursuit of large torque or high output ripple-quality, the type combination of small backlash and symmetrical relief-groove shall be selected, etc. It is concluded that the obtaining method of output characteristics is simpler, the principle is clearer, the form is more concise, and the results are more reliable.